A feasibility double-blind trial of levothyroxine vs. levothyroxine-liothyronine in postsurgical hypothyroidism - Phan, Giao Q.; Yavuz, Sahzene; Stamatouli, Angeliki M.; Madan, Ritu; Chen, Shanshan; Grover, Amelia C.; Nilubol, Naris; Bedoya, Pablo; Trankle, Cory; Markley, Roshanak; Abbate, Antonio; Celi, Francesco S. (Frontiers in Endocrinology, 2025)
ContextDespite normalization of Thyrotropin (TSH), some patients with hypothyroidism treated with Levothyroxine (LT4) report residual symptoms which may be attributable to loss of endogenous triiodothyronine (T3).ObjectiveFeasibility trial LT4/liothyronine (LT3) combination vs. LT4/placebo in post-surgical hypothyroidism.DesignDouble-blind, placebo-controlled, 24-week study.SettingAcademic medical centerPatientsIndividuals with indications for total thyroidectomy and replacement therapy.InterventionsLT4/LT3 5 mcg (twice daily) vs. LT4/placebo (twice daily). LT4 was adjusted at 6- and 12-weeks with the goal of baseline TSH ± 0.5 mcIU/ml.Main Outcome MeasuresChanges in body weight, cholesterol, TSH, total T3, free tetraiodothyronine (T4). Cardiovascular function, energy expenditure, and quality of life (ThyPRO-39) were assessed in patients who completed at least the 3-month visit, last measure carried-forward.ResultsTwelve patients (10 women and 2 men), age 51 ± 13.8 years (7 LT4/placebo, 5 LT4/LT3), were analyzed. No significant differences were observed in TSH. Following thyroidectomy, LT4/placebo resulted in higher free T4 + 0.26 ± 0.15 p<0.005 and lower total T3 -18 ± 9.6 ng/dl p<0.003, respectively, not observed in the LT4/LT3 group. The LT4/placebo group had a non-significant increase in body weight, +1.7 ± 3.8 Kg, total- and LDL-cholesterol +43.1 ± 72.8 and +32.0 ± 64.4 mg/dl. Conversely the LT4/LT3 group changes were -0.6 ± 1.9 Kg, -28.8 ± 49.0 and -19.0 ± 28.3 mg/dl, respectively, all non-significant. Non-significant improvement were observed in ThyPRO-39 measures in both groups, while energy expenditure, and diastolic function increased in the LT4/LT3 group.ConclusionsIn this group of patients with post-surgical hypothyroidism LT4 replacement alone does not normalize free T4 and total T3 levels and is associated with non-significant increase in weight and cholesterol. LT4/LT3 combination therapy appears to prevent these changes.Clinical Trial RegistrationClinicatrials.gov, identifier NCT05682482.